2012
DOI: 10.1007/s13139-012-0161-9
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Metabolic Tumor Volume Measured by 18F-FDG PET/CT in Operable Primary Breast Cancer

Abstract: PET indices seem to be useful in the preoperative evaluation of prognosis in patients with operable primary breast cancer. NSUV, NMTV and TMTV might be considerable factors associated with patient outcome in operable breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 23 publications
0
27
2
Order By: Relevance
“…PET/CT is also useful in evaluating treatment response and recurrence [2]. Parameters of 18F-FDG PET/CT, including maximum standardized uptake value (SUV max ) and metabolic tumor volume (MTV), are considered to be prognostic factors for survival and predictors of treatment response [3,4,5,6,7]. Tumor heterogeneity measured by 18F-FDG PET/CT has been emphasized in various malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…PET/CT is also useful in evaluating treatment response and recurrence [2]. Parameters of 18F-FDG PET/CT, including maximum standardized uptake value (SUV max ) and metabolic tumor volume (MTV), are considered to be prognostic factors for survival and predictors of treatment response [3,4,5,6,7]. Tumor heterogeneity measured by 18F-FDG PET/CT has been emphasized in various malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Groheux et al [15] reported that TLG is superior to SUVmax as a predictor of outcome in patients with ER-positive/HER2-negative breast cancer. In addition, only one study has considered the role of MTV as a prognostic factor in breast cancer patients [6]. However, there are no studies that evaluated the correlation among WB semiquantitative PET/CT data, DFS and OS in patients with stage II/III breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…16 is a good predictor of disease progression and overall survival (OS). The usefulness of other measures, such as metabolic tumour volume (MTV) and total lesion glycolysis (TLG), for determining the aggressiveness of tumours and for predicting treatment response has been evaluated; however, although preliminary findings are encouraging, associations between these measures and prognosis have not been found consistently [6,7]. The aim of our study was to investigate whether SUVmax, MTV and TLG, and whole-body (WB) SUVmax, WB MTV and WB TLG can be considered prognostic factors predicting disease-free survival (DFS) and OS in patients with stage II/III breast cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Growing evidence suggests that MTV and TLG may have prognostic value in several solid tumors . However, the use of these volumetric metabolic parameters in the prognosis of BC remains limited and the results are somewhat controversial, and criteria for these parameters have yet to be established …”
Section: Introductionmentioning
confidence: 99%